Branding Strategies for Candy Products on Instagram: A Consumer Culture Analysis of “KIS MINT” through @kisduludong - Kumala Hayati; Nurfarah Nidatya; Garcia Krisnando Nathanael (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Kis Mint, traditionally known as a candy brand for children, aims to expand its market reach to teenagers and adults while maintaining a competitive position in the industry. With over 163 million users, Instagram serves as a strategic platform for branding and consumer engagement. This study examines Kis Mint’s branding strategy on Instagram (@kisduludong) through the lens of consumer culture. Using a qualitative case study approach, data were collected through unstructured interviews, participant observation, and digital document analysis. The findings reveal that Kis Mint employs three key branding strategies: (1) aligning its marketing with the lifestyles of teenagers and adults who carry candy as a daily necessity, (2) catering to diverse taste preferences by offering fresh and sweet flavours for teenagers and sour variations for adults mindful of sugar intake, and (3) utilizing individual packaging to maintain a mature appeal for adult consumers. Additionally, Kis Mint maximizes Instagram’s features, particularly its feed, to highlight product benefits such as breath-freshening properties while fostering social interaction through interactive content like quizzes. These strategies collectively enhance Kis Mint’s brand positioning and engagement on social media.